A Unique Case of Chronic Myeloid Leukemia Relapsing as an Isolated Blast Phase in the CNS and Literature Review - Deb, MD, PhD, Pratik Q.; Nimchinsky, MD, PhD, Esther; Agarwalla, MD, PhD, Pankaj K; Kra, MD, Joshua; Cai, MD, PhD, Donghong; Baisre, MD, Ada (North American Journal of Medicine and Science, 2023)
Chronic myeloid leukemia (CML) is one of the most common hematologic malignancies characterized by the Philadelphia chromosome and pathogenic fusion protein BCR-ABL1. CML is considered a treatable malignancy with a favorable outcome. However, one of the familiar and often fatal sequelae of this disease, is when the chronic phase leukemia evolves into the blast phase in the peripheral blood or bone marrow, or in extramedullary proliferation of blasts with myeloid or less commonly lymphoid differentiation. Extramedullary blast phase of CML is a rare phenomenon. Here, we report a case of a patient with CML, BCR-ABL1–positive, who had achieved hematologic and cytogenetic remission, who presented with neurological symptoms including dizziness, weakness, and headache. An MR of the brain showed diffuse cerebral and cerebellar leptomeningeal enhancement, and small regions of parenchymal enhancement in the left frontal lobe. A brain biopsy of an area of leptomeningeal enhancement showed a leptomeningeal infiltrate of blasts and immature myeloid cells, weakly positive for myeloid markers such as myeloperoxidase, CD117 and CD68, and was negative for CD3, PAX-5 and CD20. Fluorescent in-situ hybridization performed using dual fusion was positive for BCR-ABL1 translocation in the leptomeningeal infiltrate, indicative of a t(9;22) involving these two genes. The patient is being treated with intrathecal chemotherapy at the time of this report. This case documents an unusual presentation of known sequelae of CML. Awareness of this phenomenon will help us diagnose and manage this complication in the future. [N A J Med Sci. 2023;16(1):014-018. DOI: 10.7156/najms.2023.1601014] Key Words: Chronic myeloid leukemia, Blast crisis, Acute leukemia, Blood cancer, Malignancy